The European Network for Translational Research in Atrial Fibrillation. (November 2012) - Hatem, Stéphane; Schotten, Ulrich; Rohr, Stephan; Dobrev, Dobromir; Ravens, Ursula; Goette, Andreas; Pieske, Burkert; Kockskämper, Jens; Lendeckel, Uwe; Casadei, Barbara; Kirchhof, Paulus; Müller, Frank Ulrich; et al.
The initiation and perpetuation of atrial fibrillation (AF) can be regarded as a complication of a progressive transformation of atrial structure and function. This transformation is the result of complex changes at the molecular, cellular and organ levels, leading to the profibrillation arrhythmic mechanisms in AF. Numerous individual and environmental factors are probably involved in this process. Therefore, progress in the diagnosis, prevention and treatment of AF requires highly integrative research from the benchtop to bedside and from specific signaling pathways and electrophysiological mechanisms to population-based studies. The European Network for Translational Research in Atrial Fibrillation was formed to provide this variety of expertise and has identified central research objectives for improvements in AF prevention and therapy.